AeroMEMS sensor array for high-resolution wall pressure measurements - Berns, A.; Buder, U.; Obermeier, E.; Wolter, A.; Leder, A. (Sensors and actuators. A. Physical., 2006)
The measurement of wall pressure and wall pressure fluctuations in fluid mechanics is of great importance for the investigation of turbulent flow phenomena. This paper is focused on the design, fabrication and test of a micro electromechanical system (MEMS) pressure sensor array for high-resolution wall pressure measurements in turbulent flows. In contrast to pressure sensor arrays in literature this array is highly sensitive and can be flush mounted on top of a cylinder without using pin holes and flexible tubes. Employing silicon-on-insulator (SOI) technology and deep silicon etching the sensors developed achieve a pressure resolution of 0.5 Pa. Three different types of sensors, featuring a diaphragm thickness of 3 μm and diaphragm sizes of 500 μm, 700 μm, and 900 μm (square diaphragm), have been fabricated and characterized. Simulation of the dynamic behavior yields resonance frequencies of 50 kHz (900 μm-diaphragm), 82 kHz (700 μm-diaphragm), and 160 kHz (500 μm-diaphragm). Sensitivities of 12 μV/(VPa) (900 μm-sensor), 7 μV/(VPa) (700 μm-sensor), and 3 μV/(VPa) (500 μm-sensor) are obtained in measurement ranges of ±200 Pa, ±500 Pa, and ±1 kPa, respectively, featuring a non-linearity of less than 1%. The array was flush mounted on a cylinder (radius 60 mm, height 240 mm) and tested in a wind tunnel.